Revisiting and extending a response latency measure of inclusion of the other in the self. Issue 1 (1st September 2016) - Zickfeld, Janis H.; Schubert, Thomas W.
ABSTRACT: Although the concept of inclusion of the other in the self (IOS) has been successfully assessed with explicit self-report measures, implicit procedures have been neglected in past literature. The present article explores the validity of such an implicit measure by proposing several extensions and adaptions. We addressed methodological problems of a me/not-me response latency task developed in this literature by proposing changes in material, calculation of indices and implemented the task in an online environment. We also addressed earlier problems with statistical power and proposed a more powerful way of statistical analyses using mixed models. The me/not-me task is based on the idea that higher overlap between self and other traits results in faster response times of characterizing such a trait as descriptive of the self. This relationship should be observed for close others but not for non-close others. In a sample of 339 U.S American adults, we experimentally manipulated the nature of the target (close vs. distant) and participants engaged in the adapted me/not-me paradigm. Results indicated that trait match had a stronger negative effect on response times for participants in the close condition. The effect was also stronger for participants rating the target higher on the IOS self-report scale. We also provided convergent validity of the me/not-me procedure with other constructs ostensibly measuring interpersonal closeness . Future applications and possible limitations are discussed.